Induction of Apoptosis and G2/M Phase Cell Cycle Arrest by Antimicrobial Peptide HepTH1-5 - Khamsah Suryati, Mohd; Abd Manaf, Ali; Wan Atirah, Azemin (2015)
Antimicrobial peptides (AMPs) have been reported to display multifunctional properties as potential therapeutic agents. They exhibit rapid killing and a broad spectrum of activity against Gram-positive and Gram-negative bacteria, fungi, parasites, enveloped viruses and tumour cells. An AMP, hepcidin TH1-5 (HepTH1-5) is a small and cationic peptide was shown as important innate immune defense in Tilapia (Oreochromis mossambicus). Recent studies have shown that synthetically derived HepTH1-5 displayed cytotoxic effect on tested cancer cell lines. In this study, we aimed to investigate the cytotoxic and apoptosis effects of HepTH1-5 on HL-60, HepG2 and HeLa cells and compare to noncancerous cell lines, Chang and NIH/3T3. We also investigated the effect of this peptide on cell cycle. Cytotoxic assay by MTT revealed that HepTH1-5 is highly cytotoxic on HepG2, HeLa and HL-60 cells with IC50 of 8.58 x10-4 µM, 0.011 µM and 0.0858 µM respectively. These results also comparable with methotrexate, a standard chemotherapy drug. Intriguingly, it does not show significant cytotoxicity against normal cells. Apoptogenic effects of HepTH1-5 were studied by acridine orange/propidium iodide staining and revealed that after 24h treatment, 61.2% of HepG2 cells were in early apoptosis, 20.7% in late apoptosis while 1% of cells were in necrosis. In contrast, after 24h treatment with methotrexate, only 18.2% of cells were in early apoptosis, whereas 76.3% were in late apoptosis. This trend was continued after 48h treatment but prolonged incubation of 72h saw a dramatic change in the apoptotic effect where less than 12% of cells were at early apoptosis while more than 79.7% were at late apoptosis. Cell cycle analysis on HepG2 cells showed that HepTH1-5 was able to block cell at G2/M phase significantly but not in HeLa while methotrexate arrest cells at G0/G1 phase. This data revealed that apoptosis effect of HepTH1-5 and methotrexate in cell cycle might occur at different mechanism. Taking all the data together, it was found that HepTH1-5 significantly triggers apoptosis in cancerous cells and it shows that this peptide could potentially be developed as anticancer agent.